Measuring Tourism Economic Impact Approach with Keynesian Multiplier: Case on Prambanan Temple - Nining Yuniati; A. Citra Rahadevi (Politeknik Siber Cerdika Internasional, 2026)
Background: One way to assess the economic benefits of tourism is by determining the multiplier value, and one of the most widely applied valuation approaches is the Keynesian multiplier model. Although several studies have examined the multiplier effect of tourism in general, limited empirical research has specifically examined Prambanan Temple as a heritage tourism destination with the highest visitor volume in Yogyakarta, indicating a notable gap in the literature. Objective: The Keynesian multiplier uses inputs involving the direct impact of expenditure, or Tourist Expenditure (E), and local business income in the tourism sector (D); the indirect impact based on the income or wages of local labor in the tourism sector (N); and the induced impact based on tourist spending on local products (U). Method: The Keynesian multiplier is formulated as (D + N + U)/E. A sample of 100 tourists and 10 informants representing tourism businesses and tourism workers was selected as the parties to be interviewed. Result: The analysis yielded a Keynesian income multiplier of 6.75, indicating that every IDR 965,630 spent by an average tourist generated an estimated total economic impact of IDR 6.52 million within the local tourism economy. A multiplier value exceeding 1 indicates that Prambanan Temple, as a tourism destination, demonstrates a significant economic impact in improving the economic welfare of the surrounding community. Conclusion: In measuring job creation, a ratio of 1:4 was obtained, meaning that the arrival of every one tourist can create four job opportunities.